2020
DOI: 10.1016/j.ajic.2020.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Viral and bacterial coinfection among hospitalized children with respiratory tract infections

Abstract: Background: The epidemiology of Mycoplasma pneumoniae (MP) and local dominant etiologies of pathogens that cause respiratory tract infections (RTIs) among central China children (≤14 years old) hospitalized are poorly understood. Methods: A total of 10,429 specimens were analyzed, and IgM antibodies against 9 respiratory pathogens including MP were detected using indirect immunofluorescence assay from serum. Results: It showed that 59.3% of the enrolled children were positive for at least 1 pathogen; highest d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 35 publications
(33 reference statements)
2
11
2
Order By: Relevance
“…In our study, children aged 1-3 years were most likely to develop acute respiratory tract infection symptoms in both 2019 and 2020. In addition, the positive rate of MP was detected more commonly in children 3 years of age or older than in younger children, which was corroborated by previous epidemiological studies ( Jain et al., 2015 ; Schildgen et al., 2018 ; Liu et al., 2020 ). However, the positive rate of MP in our study is different from that in other previous studies ( Gao LW et al., 2019 ; Jiang et al., 2020 ), which may be due to differences in MP detection methods and enrolled populations.…”
Section: Discussionsupporting
confidence: 85%
“…In our study, children aged 1-3 years were most likely to develop acute respiratory tract infection symptoms in both 2019 and 2020. In addition, the positive rate of MP was detected more commonly in children 3 years of age or older than in younger children, which was corroborated by previous epidemiological studies ( Jain et al., 2015 ; Schildgen et al., 2018 ; Liu et al., 2020 ). However, the positive rate of MP in our study is different from that in other previous studies ( Gao LW et al., 2019 ; Jiang et al., 2020 ), which may be due to differences in MP detection methods and enrolled populations.…”
Section: Discussionsupporting
confidence: 85%
“…In our study, the detection rate of respiratory viruses in children with ARI was 24.96 %. In other studies, the rates ranged from 24.5 to 72.3 % in other regions of China and other countries [ 4 , 5 , 7 9 ], which indicates the complexity and diversity of ARI etiology. RSV and IFA were the two most frequently detected viruses in this study.…”
Section: Discussionmentioning
confidence: 79%
“…A better understanding of the epidemiological and clinical characteristics of respiratory infections leading to ARI is critical for the successful implementation of prevention, control, and treatment strategies. Although some studies on the epidemiology of respiratory infections including ARI have recently been reported for local areas of China [ 4 , 5 ], there have been few articles reporting the epidemiological and clinical characteristics of respiratory viruses from multiple hospitals. To better understand the nature of respiratory infections in children, we analyzed epidemiological and clinical characteristics of respiratory infections in pediatric patients aged 0–18 years from 16 hospitals in Guangdong, China in 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Respiratory tract infections pose a critical health problem, as they are a leading cause of mortality in children globally, especially in developing countries, causing approximately 19% of all deaths among children under five years and 8.2 % of all disability and premature mortality. New respiratory infections have become increasingly significant in modern infectious diseases, since the acute severe respiratory syndrome outbreak in 2003, the influenza A (H1N1) pandemic in 2009, and the influenza A (H7N9) pandemic in 2013 24 . Acute respiratory viral infections usually start in the upper respiratory tract as the port of entry is the nose, mouth, or eyes, and spread to the lower parts of the airways occurs within two to four days 25 .…”
Section: Background and Current Scenario Of Epidemics Of Acute Respiratory Viral Infectionsmentioning
confidence: 99%